'The Foreign Within': State–Civil Society Relations in Russia. Issue 7 (8th August 2020) - Stuvøy, Kirsti
Abstract: The development of Russian civil society is linked to authoritarian government, fear of 'colour revolutions' and the 'sovereign democracy' that legitimises state control of civil society. This article acknowledges the narrowing room for manoeuvre of contemporary Russian civil society and discusses NGOs' practices in the context of government pressures, the politicisation of transnational connections and the increasing geopolitical tension surrounding Russia. It describes the localisation and depoliticisation of Russian NGOs as well as their disruptive practices, and explains how narrowing civil society identities inform the self-governing of NGOs. Finally, it argues that seeing Russian civil society in simple dichotomies further narrows these identities.